Self-Incompatibility and Embryo Development in Astragali Radix - Kim, Y.G. (National Institute of Horticultural and Herbal Science, Ginseng Research Division, Eumsung, Republic of Korea), E-mail: kimyk@rda.go.kr; Yu, H.S. (National Institute of Horticultural and Herbal Science, Ginseng Research Division, Eumsung, Republic of Korea); Seong, N.S. (National Institute of Horticultural and Herbal Science, Ginseng Research Division, Eumsung, Republic of Korea); Park, H.K. (National Institute of Horticultural and Herbal Science, Ginseng Research Division, Eumsung, Republic of Korea); Son, S.Y. (Chungbuk National University, Cheongju, Republic of Korea) (Hanʼguk Yakyong Changmul Hakhoe chi, 2008)
This study was conducted to determine the characteristics of fertilization process and embryo development of Astragalus membranaceus Bunge (Astragali Radix) to provide basic data needed in its breeding. A. membranaceus showed poor seed setting when self-pollination was induced. When artificial pollination was induced, it showed less than 5% bearing in late August, but more than 13% bearing from the beginning of September 4th. The flower size was about 17.0 mm × 4.0 mm and pistils and stamens had the same length of 15.0 mm at flowering stage. When self-pollination or cross-pollination was induced, pollen tubes extended to an ovule. While pollen tube was extending to the ovule, reproductive cell split and formed two male generative nuclei and a vegetative nucleus. In the case of self-pollination, fertilized embryo was not observed, but was formed in the case of cross-pollination. A. membranaceus is noted to have zygote self-incompatibility. In the case of cross-pollination, fertilization was observed in 6 to 8 h after pollination, where apical cell derivatives split after fertilization. A spherical pro-embryo was then formed three days after fertilization. The seed attained full shape with a seed coat showing its distinctive contour 15 days after fertilization. Thus, A. membranaceus in Leguminosae family is found to have zygote selfincompatibility although its flower shape is shown to match the self-compatibility plant.